Defining 'quality' from the patient's perspective: findings from focus groups with Medicaid beneficiaries and implications for public reporting. (28th April 2016) - Theis, Ryan P.; Stanford, Jevetta C.; Goodman, J. Robyn; Duke, Lisa L.; Shenkman, Elizabeth A.
Abstract: Background: With an increased emphasis on patient‐centred outcomes and research, investigators seek to understand aspects of health care that are most important to patients. Such information is essential for developing report cards that present health‐care quality information for consumers, which many states are adopting as a strategy to promote consumer choice. Objective: This study examined the processes that women in Medicaid follow for selecting health plans and explored their definitions of 'good' and 'poor' quality health care. Design: We conducted focus groups with Medicaid beneficiaries in four Texas communities, using quota sampling to ensure representation of different racial/ethnic, eligibility and geographic groups. Results: We conducted 22 focus groups with 102 participants between October 2012 and January 2013. In a free‐list exercise, 'doctors' represented the most important aspect of health care to participants, followed by cost, attention, coverage and respect. Discussions of health‐care quality revealed an even mix of structural factors (e.g. timeliness) and interpersonal factors (e.g. communication), although few differences were observed by beneficiary characteristics. Participants linked themes in their overall framing of 'quality' – revealing processes of care that affect health outcomes (e.g. discontinuity of care resulting from poor communication with providers) and which were often mediated by advocate providers who assisted patients experiencing barriers to services. Discussion and conclusions: Findings support other studies that highlight the importance of the patient–provider relationship. Patient‐centred definitions of health‐care quality can complement predominant provider‐centred conceptual frameworks and better inform initiatives for public reporting of quality measures in these populations.